Resolving Changes to Freshwater Lens Systems in a "Sea of Salinity" using Multi-date Airborne EM. Issue 1 (1st December 2018) - Munday, Tim; Soerensen, Camilla
Abstract : Saline aquifers in the Murray River or SE Australia are traversed by freshwater rivers, with adjoining riparian and floodplain regions containing freshwater lenses. Bore data and more recent Airborne electromagnetic (AEM) surveys have determined that these lenses are spatially extensive, but have widely varying geometries. The maintenance of these lens systems is important as they support ecologically significant riparian vegetation communities such as Red Gum and Black Box. A more complete understanding of their hydrogeology is required to ascertain how they develop and degrade. Limited ground investigations including 14 C geochemistry have determined that the lens systems contain recent water, indicating that they are dynamic systems with their development defined by the relative rates of recharge from the river and mixing with groundwater. Changes in groundwater gradients and depth, floodplain extent, and topography are believed to control their initial location. The same controls also govern their stability. The potential of AEM systems for defining the geometry of these lens systems in 3D is considered along with an assessment of their value for monitoring variations associated with these ecosystems. The advent of "calibrated" AEM systems and robust inversion tools have given added impetus to their use for environmental monitoring. Spatio-temporal variations are observed in the near surface (top 20m) from a multi-temporal assessment of Clark's Floodplain, adjacent to the Bookpurnong irrigation area, with co-incident AEM surveys acquired between 2008 and 2015. Spatial changes in ground conductivity, attributed to changing groundwater quality have been observed. The freshwater lens systems appear to have contracted significantly over the last decade. This is attributed, in part, to land use patterns and the development of an irrigation-related groundwater mound on the highlands adjacent to the floodplain, and an increased hydraulic gradient towards the river. The results indicate the geometry of the hyporheic zone may have also changed along the river.